Securitization and Bank Credit Risk: Empirical Evidence from the US Commercial Banks - Hu, Linlin (2019)
The main objective of this dissertation is to empirically analysis the effect of securitization activities on bank risks, and the influence of other bank specific factors are also considered simultaneously. Additionally, this analysis further examines the relationship between securitization activities and long-term bank stability. The sample data selected to make analysis is the balanced data of 149 US commercial banks from 2007 to 2017, which could represent both 2007-2009 Financial Crisis period and post-crisis period. In particular, we employ panel data approach to make correlation estimation by pooled OLS method, fixed effect model and random model. From test results, we find that securitization has a significant positive effect on bank credit risk level while negatively influence bank long-term stability. That is, the more securitized assets owned by banks, the bank would be riskier and more erratic.